Penerapan Metode SDLC Waterfal Dalam Pembuatan Sistem Pendataan Peternakan Kabupaten Kampar Berbasis Web Menggunakan Framework Codeigniter - Khairul Abidin; Fenty Kurnia Oktorina; Slamet Triyanto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
To find out the development of the livestock sector, the Livestock Service Office of Kampar Regency collects data on livestock in Kampar Regency. The data is then processed in excel and then reported to the relevant agencies. Data collection with this system creates problems of difficulty in processing and searching data. The more data that is recorded, the more difficult the process of processing and searching for data. As a solution, a web-based Kampar Regency livestock data collection system was built using the codeigniter framework  and made using the php programming language and mysql database as well as a design modeled with UML (Unified Modeling Language). The purpose of this system is to facilitate livestock data collection and more efficient data processing and searching. The results can facilitate data management by the Livestock Service Office of Kampar Regency, present information about livestock in Kampar Regency and a more efficient data collection and processing process.